2005
DOI: 10.1177/153857440503900509
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of the Beneficial Effect of Changing Vascular Anastomotic Technique in Hemodialysis Access

Abstract: There is an urgent and compelling need to reduce the morbidity and expense of maintaining hemodialysis vascular access patency. We previously reported the beneficial effects of altering anastomotic technique on vascular access patency from a multicenter clinical trial. Interrupted anastomoses created with nonpenetrating clips showed significant improvement in primary, assisted primary, and secondary patencies of native vein fistulae (AVF) and synthetic arteriovenous grafts (AVG). In the current report, we prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, the breakout between incident and prevalent patients allowed for a more accurate comparison of the matched populations, given that almost one-half of the endoAVF patients in NEAT were incident at the time of fistula creation. Although we compared endoAVF costs with SAVF costs, there are limited studies within the SAVF literature comparing different AVF anastomotic techniques and associated cost of maintenance with SAVF (24). El-Gamil et al used USRDS to compare vascular access costs in freestanding office-based centers with the hospital outpatient department, but they combined SAVF and AVG outcomes, so the results can not be compared with the present study (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the breakout between incident and prevalent patients allowed for a more accurate comparison of the matched populations, given that almost one-half of the endoAVF patients in NEAT were incident at the time of fistula creation. Although we compared endoAVF costs with SAVF costs, there are limited studies within the SAVF literature comparing different AVF anastomotic techniques and associated cost of maintenance with SAVF (24). El-Gamil et al used USRDS to compare vascular access costs in freestanding office-based centers with the hospital outpatient department, but they combined SAVF and AVG outcomes, so the results can not be compared with the present study (25,26).…”
Section: Discussionmentioning
confidence: 95%
“…Due to the recent innovation of endoAVF, no prior endoAVF costing studies exist for comparison. Within the surgical AVF literature, there is also a paucity of economic studies evaluating different AVF anastomotic techniques that may have shown reduced costs associated with AVF creation and maintenance (16).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple factors that contribute to the upstream events of vascular access dysfunction: (1) the proinflammatory uremic milieu that promotes endothelial dysfunction [16,60], (2) hemodynamic stressors at the anastomosis site due to a combination of small and non-compliant vessels, low shear stress and turbulence [16,61,62], (3) vascular injury at the time of fistula or graft formation due to vessel manipulation through surgical technique or angioplasty [16,61,62], (4) a localized inflammatory response involving cytokine release and macrophage migration caused by the synthetic graft material used in the formation of the AVG [16], (5) possible genetic predisposition to neointimal hyperplasia and vasoconstriction [11,16] 6and repeat cannulation injury [16,54].…”
Section: Pathophysiology Of Arteriovenous Access Dysfunctionmentioning
confidence: 99%